Assessment of Loose Residue Entanglement in Various Patterns of Furrow Opener Arrangement - Sharma, Vineet Kumar; Singh, T. P. (Journal of Agricultural Engineering, 2018)
Poor residue handling capability of no-till drills in combine harvested rice and wheat fields during sowing of wheat in rabi and pulses in kharif is a major barrier for their extensive use. The problem aggravates more due to lesser inter-spacing between furrow openers and their arrangements on only two toolbars. A study was conducted to assess the effect of furrow opener arrangements on residue accumulation on a test setup with three toolbars and seven inverted-T type furrow openers. Six patterns of furrow opener arrangements were evaluated in combine harvested wheat field. Furrow openers in V-type arrangement of 2, 2 and 3 on front, middle and rear toolbar, respectively, (Arrangement-B) was the best in terms of residue entanglement and accumulation of 121 g.m-1 length. No residue accumulation was observed when the setup was operated under chopped residue condition with same arrangement. Residue flow percentage was 100% for this arrangement. The result suggested arranging the furrow openers on three toolbars with wider furrow opener spacing to minimize the residue accumulation while drilling pulse crops under no-till residue condition after wheat harvesting.